Democratising smart cities? Penta-helix multistakeholder social innovation framework - Calzada, I (MDPI, 2020)
The smart cities policy approach has been intensively implemented in European cities under the Horizon 2020 programme. However, these implementations not only reduce the interdependencies among stakeholders to technocratic Public-Private-Partnership (PPP) models, but also fail to question the identities of strategic stakeholders and how they prioritise their business/social models. These aspects are putting democracy at stake in smart cities. Therefore, this article aims to unfold and operationalise multistakeholders’ policy frameworks from the social innovation perspective by suggesting the ex-novo penta-helix framework—including public, private, academia, civic society, and social entrepreneurs/activists—to extend the triple and quadruple-helix frameworks. Based on fieldwork action research conducted from February 2017 to December 2018—triangulating desk research, 75 interviews, and three validation workshops—this article applies the penta-helix framework to map out five strategic dimensions related to (i) multistakeholder helix framework and (ii) the resulting business/social models comparatively in three follower cities of the H2020-Replicate project: Essen (Germany), Lausanne (Switzerland), and Nilüfer (Turkey). For each case study, the findings reveal: (i) a unique multistakeholder composition, (ii) diverse preferences on business/social models, (iii) a regular presence of the fifth helix as intermediaries, and (iv) the willingness to experiment with democratic arrangements beyond the hegemonic PPP.